(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: In family medicine, home visits are a tangible manifestation of patient-centred care, allowing physicians to comprehensively understand patients’ circumstances and cater to their medical and psychosocial needs. However, a recent decline in general practitioner home visits has raised significant concerns about the potential impact on care quality, particularly for older patients. General practitioners’ age, gender and attitudes may play a role. Attitudes refer to positive or negative thinking or feelings about something typically reflected in a person’s behaviour. AIMS: To study the effects of age and gender (i.e. predictors) on the number of home visits conducted during a typical week of work (i.e. outcome) by general practitioners in Canton Ticino, Switzerland. To investigate whether attitudes (i.e. mediators) mediate the relationship between age and home visits, controlling for gender. METHODS: A cross-sectional study was conducted from June to October 2023 on 142 family doctors (28% women) with an average age of 56.42 years (standard deviation [SD] = 11.51, range 36–83). Correlations between variables and a t-test with gender were conducted. A mediation analysis was performed to examine the potential association in which the attitudes may mediate the relationship between age and home visits, controlling for gender. RESULTS: Older physicians conducted more home visits in a typical week (r = 0.32, p <0.001) than younger physicians, while female doctors conducted fewer visits (M = 2.39±1.8) than males (M = 4.09±2.9), t(100.8) = 3.77, p <0.001. The mediation analysis suggested that younger general practitioners tend to have more negative attitudes towards home visits, which in turn leads to a decrease in the number of home visits they make in a typical week (indirect effect B = 0.02). CONCLUSION: There is a generational and gender effect on home visit practice in family medicine. Moreover, younger doctors hold more negative attitudes towards home visits.